Development and validation of a scale to measure attitude of people toward men in nursing profession - Sharma K Sharma; Shiv Kumar Mudgal (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Ancient history mentions the dominance of men in nursing; however, now nursing has a feminine image, and globally more than 90% of nursing workforce is females. Recently, more number of males are attracted to nursing, but there is a paucity of literature on the attitude of people about men in nursing may be because of a lack of measurement scales available for this purpose. The aim of this study was to develop and validate a new scale measuring attitude of people toward men in nursing. MATERIALS AND METHODS: The present study was conducted at a tertiary care hospital and used an exploratory sequential design with an instrument development model. A total of 400 participants were selected using the simple random sampling technique. The reliability, content validity, face validity, and construct validity of this newly developed scale were computed. For data analyses SPSS AMOS version 23 was used for performing exploratory and confirmatory factor analyses. RESULTS: The new scale "AMnQ" consists of 15 items under three factors: (I) nursing is feministic and professionally low, (II) higher suitability of male nurses in technical and challenging situations, and (III) synonymy of empathy and care with a female. The final model with 15 items of AMnQ scale was validated by confirmatory factor analysis and showed a good fit to data. The Cronbach's α for the overall scale was 0.87, and for Factors I, II, and III, it was 0.80, 0.88, and 0.89, respectively. CONCLUSIONS: The "AMnQ" is a valid, reliable scale to assess the attitude of patients, nurses, physicians, and nursing students toward men in nursing. There is an assumption that nursing is a feminine profession; therefore, a valid and reliable scale to measure the attitude of people toward men in nursing will help to generate pieces of evidence on this subject, so that policymakers can make unbiased decisions on liberalizing entry of men in nursing.